Income adequacy among creative professionals—An interplay of identities and skills - Stenholm, Pekka (Wiley, 2025)
The financially challenging work of creative professionals is a widely recognized concern, and uncovering the root causes of such challenges requires more explorations into the impact of personal factors on income generation. Accordingly, we investigated the significance of 400 creative professionals' entrepreneurial or artistic identities and business skills in their income adequacy on the basis of role identity theory. Our findings show that business skills support the likelihood of income adequacy but that artistic identity reduces it. The combination of entrepreneurial identity with business skills increases income adequacy, whereas entrepreneurial identity alone has no influence. These results point to the complexity of individuals' income formation and the need to study the outcomes of different work identities and their interplay with various skills. They imply that assuming an artistic identity can be an economic liability. Hence, our study implies that enabling creative and innovative work to prosper necessitates that creative professionals develop an adaptive, artistic–entrepreneurial meta-identity, in addition to enhancing their business skills, so that they can adjust between possible selves in different situations and work environments.